Pendampingan Penyusunan Laporan Keuangan Amal Usaha Muhammadiyah (AUM) Pendidikan Terintegrasi Dengan PDM Kota Batu - Jati, Ahmad Waluya; Latifah, Sri Wahjuni; Wardatul, Wardatul (Universitas Muhammadiyah Malang, 2024)
Purpose – Education AUM is the largest in number compared to other AUMs. The Batu City education AUM consists of seven schools that are partners in this service. As per ISAK (Interpretation of Financial Accounting Standards) number 335, the partner has failed to submit a financial report. In addition to not filing a financial report, the partner is still only able to record cash in and cash out. It means that performance cannot be compared to last year's performance, nor can the efficacy and efficiency of the budget that has been set be determined. To further compound the inefficiency of financial report preparation, a large number of these service partners continue to prepare financial statements using Excel rather than accounting software. Their failure to submit financial reports has had an additional effect. Design/methodology/approach – Methods for problem-solving are carried out in various stages, namely: socialization, discussion, training, mentoring, and evaluation. Findings – Based on this activity, it can be concluded that there is an increase in the knowledge of financial governance and the expertise of partners in preparing financial reports using integrated accounting software for the financial statements of the Muhammadiyah regional leadership of Batu City. Originality/value – This service is carried out to help schools under the management of AUM Education prepare financial reports in accordance with ISAK (Interpretation of Financial Accounting Standards).